Learning to Teach Outside the Box: Exploring Newness in Literacies Pedagogies in a Pandemic - McKee, Lori; Murray-Orr, Anne; Throop Robinson, Evan (Language and Literacy / Langue et littératie)

(untitled) (Language and Literacy Researchers of Canada, 2023)
This article explores the innovative lesson planning assignments of preservice teacher, Marie, as part of an alternate teaching practicum during the pandemic closure of schools in Spring 2020. Marie viewed this shift in context as an opportunity to “think outside of the box”, to be creative and divert from a traditional lesson planning template. As we read the examples from Marie’s lesson plan assignments, we think with posthumanist theories of entanglement, intra-actions and the producing of newness in literacies pedagogies. We share data that show the entanglements of more-than-humans and humans within the innovative lesson plan format. In exploring Marie’s lesson plan redesigns and her reflections on them, we consider the ways these pedagogies were produced through the intra-actions of assignment criteria, provincial curricula, Marie’s knowledge of her students, families, available learning materials, and pandemic conditions. We consider how the implications of this lesson format contribute to newness in our ways of thinking and doing as teacher educators of literacies.